Enoch’s Vision of the Heavenly Temple (1 En. 14:8–25) Reconsidered - Bokhorst, Mirjam Judith (The Biblical Annals, 2024)
The paper focuses on a reexamination and reassessment of the textual evidence of Enoch’s Vision of the Heavenly Temple and of its classical interpretation as a heavenly temple complex. In line with the common scholarly opinion, 1 En. 14:8–25 has so far been interpreted in the sense of a bipartite or even tripartite temple which resembles the earthly temple in Jerusalem not only in structure but also in appearance. In contrast, this paper claims that this passage of the Book of the Watchers provides a twofold vision of two different temples, namely the inferior earthly temple and the ideal heavenly sanctuary. In this way, it articulates one of the most radical temple critiques of ancient Judaism. This interpretation is based on a careful textual analysis and a meticulous discussion of the individual elements of, in particular, the first house, taking into account other ancient Jewish sources such as Ezekiel, Haggai and the Animal Apocalypse which partially have been ignored so far but provide a helpful and illuminating background for the interpretation of Enoch’s Heavenly Vision.